2020
DOI: 10.1200/jco.19.03120
|View full text |Cite
|
Sign up to set email alerts
|

Management of Male Breast Cancer: ASCO Guideline

Abstract: PURPOSE To develop recommendations concerning the management of male breast cancer. METHODS ASCO convened an Expert Panel to develop recommendations based on a systematic review and a formal consensus process. RESULTS Twenty-six descriptive reports or observational studies met eligibility criteria and formed the evidentiary basis for the recommendations. RECOMMENDATIONS Many of the management approaches used for men with breast cancer are like those used for women. Men with hormone receptor–positive breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 68 publications
3
132
0
9
Order By: Relevance
“…Our study adds to what is known about the experience of men with breast cancer who are prescribed ET [15,[69][70][71][72][73]. Compared with women, men in our study were less likely to report side effects but more likely to discontinue therapy.…”
Section: Discussionmentioning
confidence: 62%
“…Our study adds to what is known about the experience of men with breast cancer who are prescribed ET [15,[69][70][71][72][73]. Compared with women, men in our study were less likely to report side effects but more likely to discontinue therapy.…”
Section: Discussionmentioning
confidence: 62%
“…Because there is still no certain evidence such as randomized clinical trials focusing on male breast cancer patients, treatment approaches are extrapolated from studies of treatment for women breast cancer patients [10]. Adjuvant chemotherapy and HER-2 targeted therapy is suggested for MBC patients who are at substantial risk for recurrence and death since observational cohort studies have suggested improved survival among them [11,12]. Although no randomized trials have evaluated the role of radiotherapy in men, observational studies have suggested a bene t in men with positive nodes after mastectomy [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Because there is still no certain evidence such as randomized clinical trials focusing on male breast cancer patients, treatment approaches are extrapolated from studies of treatment for women breast cancer patients [10]. Adjuvant chemotherapy and HER-2 targeted therapy is suggested for MBC patients who are at substantial risk for recurrence and death since observational cohort studies have suggested improved survival among them [11,12]. Although no randomized trials have evaluated the role of radiotherapy in men, observational studies have suggested a bene t in men with positive nodes after mastectomy [13,14].…”
Section: Case Presentationmentioning
confidence: 99%